Preparation, and electrical, magnetic and thermal investigation of polypyrrole-chitosan composite and polypyrrole-chitosan-iron oxide polymer nanocomposite - Amin, Jamileh (2013)
Conducting polymer composite based on Polypyrrole-Chitosan (PPy-CHI) and Polypyrrole-Chitosan-Iron oxide nanoparticles (PPy−CHI−Fe3O4) nanocomposite were prepared by using in-situ chemical polymerization method. (PPy−CHI) composites and (PPy−CHI−Fe3O4) nanocomposite were prepared with various percentages of CHI and Fe3O4 ranging from 0.0% (w/v) to 0.9% (w/v) and 0 wt% to 15wt% respectively. Results from conductivity experiments revealed that the highest conductivity was obtained from PPy−CHI−Fe3O4 nancomposite prepared from 0.1 % (w/v) CHI, 3 Molar PPy and 3wt% Fe3O4 in 30 minutes at room temperature The X-ray diffractogram of PPy and CHI illustrated a broad scattering peak for PPy and two scattering peaks of almost equal intensity for CHI which is due to their highly amorphous and semi-crystallity structure respectively. The XRD spectra for PPy-CHI composite was almost similar to those of PPy with a broad scattering at around 25°-26° indicating an amorphous structure. The XRD spectrum of PPy−CHI−Fe3O4 nanocomposite demonstrated similar to those observed from PPy and PPy−CHI composite matrix especially in the lower weight percentage of Fe3O4. However, as the nanoparticle loading increased, the characteristic peaks of Fe3O4 begun to dominate the nanocomposite spectra indicating to some uncoated Iron oxide nanoparticle which was confirmed by Energy-Dispersive X-ray (EDX) and transmission electron microscopy (TEM). The Fourier transform infrared spectroscopy (FT-IR) spectra of PPy−CHI and PPy−CHI−Fe3O4 illustrated almost the same characteristic positions of IR absorption bands similar to those of PPy. The small shift of PPy in the PPy−CHI composites is due to the identical peaks of PPy and CHI while in the PPy−CHI−Fe3O4 nanocomposites, the matrix layer of polypyrrole which covered the surface of iron oxide has absorbed most of the IR radiation. The results of Scanning Electron microscopy (SEM) and transmission electron microscopy (TEM) confirmed that the Fe3O4 nanoparticles have been coated with the layers of polymeric matrix. A distribution of discrete globular nanoparticles with almost uniform size and dimensions was exhibited in all PPy−CHI−Fe3O4 nanocomposite samples. The reduced size of PPy−CHI and PPy−CHI−Fe3O4 particles was explained by the effect of Chitosan and iron oxide, the steric stabilization effect of CHI and a core-shell structure for PPy−CHI−Fe3O4 nancomposite which was confirmed by SEM and TEM. The results of Vibrating Sample Magnetometer (VSM) revealed the magnetic properties for various PPy−CHI− Fe3O4 nanocomposites strongly depended on the concentration loading of Fe3O4. The hysteresis loops of VSM illustrated superparamagnetic behavior for all the nanocomposite of PPy−CHI−Fe3O4 with different loading Fe3O4 percentage. The Ms (saturation magnetization) and Hc (coectivity) were monitored for samples with percentage loaded of Fe3O4 from 0.1 wt% to 15 wt%. Ms increased from 0.874 emu/g to 5.97 emu/g while Hc decreased from 241.4 Oe to 194.48 Oe. The results of electron spin resonance (ESR) spectroscopy revealed a reduction in the Peak-to-peak line-width (ΔHpp) value between PPy and PPy−CHI. The adding of Fe3O4 have resulted in (ΔHpp) values increased in the order PPy−CHI <PPy−CHI−Fe3O4 (1wt%) < PPy−CHI−Fe3O4 (3wt%) > PPy−CHI−Fe3O4 (5wt %) < PPy−CHI−Fe3O4 (7wt %) < PPy−CHI−Fe3O4 (10wt %) < PPy−CHI−Fe3O4 (15wt %) at room temperature. The spin concentration (Ns) measurement of PPy−CHI−Fe3O4 with the various Fe3O4 content revealed to be larger than PPy−CHI (8×106, 1.59×107, 3×107, 2.29 ×107, 2.43×107 and 2.49×107 spin g-1 for PPy-CHI and 1wt%, 3wt%, 5wt%, 7wt% and 10wt%, of Fe3O4 respectively). The increase in percentage loading of iron oxide also resulted in better thermal stability of the nanocomposites.